Comparative Analysis of Selling Price Determination With The Cost Plus Pricing Method in Mekarsari Umkm - IZZATI, NUR; Fitriani, Dini; Suhendi, Dede; Nurhabibah, Alawiyah (Program Studi Manajemen, Fakultas Ekonomi dan Bisnis, Universitas Widya Gama, 2025)
Effective selling price determination is one of the crucial aspects in the sustainability of MSME businesses. The background of this study is the various challenges faced by MSMEs in setting competitive selling prices in the market while providing optimal profits. The main problem lies in the lack of understanding of MSME actors regarding strategic pricing methods, such as cost plus pricing which integrates all cost components and profit margins in determining selling prices. The study focuses on a comparative analysis of selling price determination using the cost plus pricing method with traditional practices that have been carried out by MSME Mekarsari. The novelty of the study lies in the provision of an application model that supports MSME actors in adopting a practical cost-based pricing method that is relevant to local market dynamics. The phenomenon studied shows a gap between production costs and selling prices which results in profit margins not being measured accurately. The qualitative descriptive method was used in this study and the primary data sources were the results of observations and interviews with MSME Mekarsari. The data analysis method uses the calculation of selling price determination using the cost plus pricing method, the full costing approach and variable costing. Empirical findings show that the application of the cost plus pricing method can produce more competitive and measurable selling prices compared to traditional methods. In addition, this study found that the understanding of MSME actors regarding the structure of production costs plays a major role in the success of implementing this method. The results of the study provide strategic recommendations for MSMEs to increase competitive advantage through data-based price and cost analysis.